Response of Soil Water Dynamics to Rainfall on A Collapsing Gully Slope: Based on Continuous Multi-Depth Measurements - Zhi-Yun Jiang (Water, 2020)
Soil water conditions play an important role in the formation of a collapsing gully, but we are still at the early stages of understanding how the soil water changes on the slope after different rainfall events due to a lack of high-frequency continuous field observations. This study aimed to reveal the response of soil water dynamics to rainfall events for different slope aspects and positions based on continuous multi-depth observations of soil water on a typical collapsing gully slope from 2017 to 2019 in Wuhua County, Guangdong Province, China. The vegetation characteristics and soil properties were investigated, and the storage of soil water was also calculated. The results showed that the dynamics and storage of soil water varied with the slope aspect, slope position and vegetation cover. The response time of the soil water to intensive rainfall events on the sunny slope was shorter than that on the shady slope, while soil water storage in the sunny slope was significantly lower than in the shady slope (p < 0.01). For the different slope positions, the soil water response time to the intensive rainfall events on the upper slope was shorter than that in the middle slope, while the soil water storage in the middle slope was significantly higher than on the upper slope. This was mainly due to the redistribution runoff from the upper slope to middle slope, delaying the process by which rainwater infiltrated into the soil layers. Moreover, vegetation significantly allayed the response of soil water dynamics to an intensive rainfall event but increased the storage of soil water, owing to the protection of soil surface from rain and conservation of high soil clay content. The bare area in the middle position of the sunny slope was speculated to be the potential source of the collapsing gully because it lacked the cover of vegetation. Our findings highlight the importance of soil water dynamics on the formation of a collapsing gully and provided valuable insights for the optimization of soil conservation and management practices for collapsing erosion.